Komunikasi Organisasi Dalam Pengembangan Kinerja Pengurus Gapoktan Pada Program Penguatan Lembaga Distribusi Pangan Masyarakat (Kasus Pada Gapoktan Di Kabupaten Subang Dan Kabupaten Bogor) - Deni.E. Kosasih; S. Sarwoprasodjo; D. Susanto (Jurnal Komunikasi Pembangunan, 2014)
Abstract Gapoktan, stands for gabungan kelompok tani, farmers group union, is a farmer economical institution, consists of several farmer’s group have specific characteristics, that an effective organizational communication is needed. The creation of good organizational communication, communication climate Gapoktan expected to be better communication and communication satisfaction of Gapoktan’s committee members will be met, so Gapoktan more competitive and high performance.The objective of study  are: (1) to identify the characteristic of the Gapoktan’s committee members, (2) to analyze the communication climate, (3) to analyze the communication satisfaction, (4) to the relationship between oganizational communication of performance development of the Gapoktan’s committee members and communication climate; and correlationship between communication climate and communication satisfaction. The results showed that: (1) Gapoktan’s committee members are having productive; they have elementary school level of formal education; they have relatively high level of non formal education, (2) most of the Gapoktan have highly communication climate, (3) most of the Gapoktan committee members have highly satisfaction in communication, (4) there is higly significant correlation between oganizational communication of performance development of the Gapoktan’s committee members and communication climate; and there is higly significant correlation between communication climate and communication satisfaction. Keyword: organizational communication, communication climate, communication satisfaction